The role of direct support professionals in asthma management. Issue Volume 40:Issue4(2015) (2nd October 2015) - Davis, Sharon R.; Durvasula, Seeta; Merhi, Diana; Young, Paul M.; Traini, Daniela; Bosnic-Anticevich, Sinthia Z.
Abstract: Background Respiratory disease is common in people with intellectual disability (ID). The inhaled route is preferred for medication administration in treating respiratory diseases, including asthma. People with ID often need assistance with taking medicines due to cognitive, physical, and sensory impairments; in supported accommodation this assistance is provided by direct support professionals (DSPs). Method A qualitative study design was used to explore DSPs' experiences with asthma medication management. Data were collected via in-depth, semistructured, face-to-face or telephone interviews. Results Key findings included the complex balance of duties undertaken by DSPs, and a lack of consistency in asthma management processes across sites. Conclusions This exploratory research suggests that DSPs are involved in asthma management and required to use clinical judgement, but are not provided with education and tools to manage asthma in, and foster correct inhaler use by, their clients. This highlights the need for tailored guidelines that integrate with the principles of the National Disability Insurance Scheme.